The Islamic debt market for sukuk securities the theory and practice of profit sharing investment - Mohamed Ariff 1940-; Iqbal, Munawar; Shamsher Mohamad (Foundations of Islamic finance, 2012)
The relatively new sukuk (or Islamic debt securities) markets have grown to more than US $800 billion over the past decade, and continue to grow at a rate of around 20-30 per cent per year